KAJIAN AIR TANAH DENGAN TEKNOLOGI GEOLISTRIK DI DESA PAD ANG KABUPATEN TANAH LAUT - Prayogo, Teguh (Jurnal Rekayasa Lingkungan)
Groundwater is water that located beneath surface. The water moves down into the ground because of gravity, passing between particles of soil, sand, gravel, or rock until it reaches a depth where the ground is fi lled, or saturated, with water. Groundwater is stored in the ground in materials like gravel or sand. To meet a demand of drinking water in the Padang Area, groundwater is one ofsolution to overcome a problem of the need of drinking water, because the availability of surface water is not suffi cient. In this paper, it will be discussed concerning characteristic and condition of ground water by applying geoelectrical technology in Padang Area, Tanah Laut district, South Kalimantan Province. Based on the result of survey in fi eld, data processing, and modeling, it can be interpretated that the existence of potential aquifer in Padang area is occupied between 15 – 40 meter and above 130 meter depth.Keywords : Groundwater, geophysical technology